Engineering geology for society and territory - Volume 4 : marine and coastal processes - Manconi, Andrea; Locat, Jacques; Huang, Yu; Canals Artigas, Miquel; Lollino, Giorgio (Springer International Publishing, 2014)
This book is one out of 8 IAEG XII Congress volumes, and deals with the processes occurring on the coastal zone, which represents a critical interface between land and sea, as the contribution of the ocean to the provision of energy and mineral resources will likely increase in the coming decades. Several related topics fit into this volume, such as: coastal developments and infrastructures; dredging and beach re-nourishment; sediment erosion, transport, and accumulation; geohazard assessment; seafloor uses; seabed mapping; exploration and exploitation of the seafloor, of the sub-seafloor, and of marine clean energies; and climatic and anthropogenic impacts on coastal and marine environments. Examples of specific themes are coastal management and shore protection, taking into account storm-related events and natural and anthropogenic changes in the relative sea level, planning of waste disposal, remedial works for coastal pollution, seafloor pipeline engineering, slope stability analysis, or tsunami propagation and flooding. The Engineering Geology for Society and Territory volumes of the IAEG XII Congress held in Torino from September 15-19, 2014, analyze the dynamic role of engineering geology in our changing world and build on the four main themes of the congress: environment, processes, issues, and approaches. The congress topics and subject areas of the 8 IAEG XII Congress volumes are: Climate Change and Engineering Geology Landslide Processes River Basins, Reservoir Sedimentation and Water Resources Marine and Coastal Processes Urban Geology, Sustainable Planning and Landscape Exploitation Applied Geology for Major Engineering Projects Education, Professional Ethics and Public Recognition of Engineering Geology <Preservation of Cultural Heritage